An efficient organic magnesium borate-based electrolyte with non-nucleophilic characteristics for magnesium–sulfur battery. Issue 12 (29th November 2017) - Du, Aobing; Zhang, Zhonghua; Qu, Hongtao; Cui, Zili; Qiao, Lixin; Wang, Longlong; Chai, Jingchao; Lu, Tao; Dong, Shanmu; Dong, Tiantian; Xu, Huimin; Zhou, Xinhong; et al.
Abstract : An efficient organic magnesium borate-based electrolyte with non-nucleophilic characteristics for magnesium–sulfur battery. Abstract : Two-electron transfer chemistry based on earth-abundant Mg and S offers great possibilities of delivering higher energy density than current Li-ion technology. The development of non-nucleophilic electrolytes that reversibly and efficiently plate and strip Mg is believed to be a major obstacle to the implementation of this divalent battery technology. In this study, we present a new type of organic magnesium borate-based electrolyte that primarily comprises tetrakis(hexafluoroisopropyl)borate anions [B(HFP)4 ] − and solvated cations [Mg4 Cl6 (DME)6 ] 2+, which was synthesized via a facile in situ reaction of tris(hexafluoroisopropyl)borate [B(HFP)3 ], MgCl2 and Mg powder in 1, 2-dimethoxyethane (DME). Rigorous analyses including NMR, mass spectroscopy and single-crystal XRD were conducted to identify the equilibrium species in the abovementioned solution. The as-prepared Mg-ion electrolyte exhibited unprecedented Mg plating/stripping performance, such as high anodic stability up to 3.3 V ( vs. Mg/Mg 2+ ), high ionic conductivity of 5.58 mS cm −1, a low overpotential of 0.11 V for plating processes and Coulombic efficiencies greater than 98%. By virtue of the non-nucleophilic nature of this electrolyte, a fully reversible Mg/S battery was constructed that displayed an extremely low overpotential of 0.3 V and a high discharge capacity of up to 1247 mA h g −1 and yielded a specific energy of approximately 1200 W h kg −1 (10 times higher that of the Chevrel benchmark) based on the weight of active sulfur. More significantly, commonly used sulfur-carbon nanotube (S-CNTs) cathodes with S contents of 80 wt% and S loadings of 1.5 mg cm −2 were demonstrated to withstand more than 100 cycles without obvious capacity decay and to enable fast conversion processes, which achieved a charging current rate of up to 500 mA g −1 . Our findings convincingly validate the pivotal role of the newly designed non-nucleophilic Mg-ion electrolyte for practical Mg/S battery chemistry.